Problems of a Subject and Object of Criminal Attack on Persons or Establishments that are under the International Protection by the Criminal Code of the Kyrgyz Republic - C. Aidarbekov (Евразийская интеграция: экономика, право, политика, 2019)
The article deals with questions of correlation of the international criminal law and the criminal legislation of the Kyrgyz Republic and issues of a subject and object of criminal attack on the persons or establishments using international protection are considered